Strategic Regimes and Equilibrium Behavior in EU Electricity Markets. A Game-Theoretic Analysis - Gkatsikos, Alexandros (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026, 2026)
The restructuring of Europe's electricity sector following Directive 2009/72/EC introduced strategic interdependence among national energy systems through liberalized market dynamics. This study applies a repeated game-theoretic framework to examine how five major EU member states - France, Germany, Italy, the Netherlands, and Spain - adjusted their price-output strategies over 2010–2023 in response to competitive pressures and institutional evolution. Each country is modelled as a strategic player choosing among four discrete strategy types based on relative price and output positions, with payoffs derived from observed electricity prices, generation volumes, and LCOE-based cost proxies. A multinomial logit model with theory-driven variable selection estimates the probability of strategic transitions conditional on current strategy, economic performance, and the post-reform institutional context. The analysis identifies High Price–High Output as the unique Nash equilibrium and Pareto-efficient outcome in every year of the study period - a result confirmed as robust to classification threshold variation through a systematic sensitivity analysis. Despite this clear payoff dominance, most countries exhibit persistent deviation from equilibrium, driven by path-dependent institutional inertia, grid constraints, and regulatory design. Germany demonstrates full and stable Nash alignment throughout the period, while France, Italy, Spain, and the Netherlands remain in behavioral clusters that diverge from the payoff-maximising configuration. These findings highlight the structural limits of market liberalization in delivering strategic convergence and carry direct implications for the 2024 EU Electricity Market Design reform and the REPowerEU renewable energy targets.